Are behavioural responses to predation cues linked across life cycle stages?. (16th November 2016) - ANDRADE, MATEUS R.; ALBENY‐SIMÕES, DANIEL; BREAUX, JENNIFER A.; JULIANO, STEVEN A.; LIMA, ERALDO
Abstract : 1. Prey organisms can perceive cues to predation hazard and adopt low‐risk behaviours to increase survival. Animals with complex life cycles, such as insects, can exhibit such anti‐predatory behaviours in multiple life stages. 2. Cues to predation risk may induce ovipositing females to choose habitats with low predation risk. Cues to predation risk may also induce larvae to adopt facultative behaviours that reduce risk of predation. 3. One hypothesis postulates that anti‐predation behaviours across adult and larval stages may be negatively associated because selection for effective anti‐predator behaviour in one stage leads to reduced selection for avoidance of predators in other stages. An alternative hypothesis suggests that selection by predation favours multi‐component defences, with both avoidance of oviposition and facultative adoption of low‐risk behaviours by larvae. 4. Laboratory and field experiments were used to determine whether defensive responses of adult and larval mosquitoes are positively or negatively associated. The study tested effects of waterborne cues from predatory Toxorhynchites theobaldi on oviposition choices and larval behaviours of three of its common prey: Culex mollis, Limatus durhamii and Aedes albopictus . 5. Culex mollis shows strong anti‐predator responses in both life stages, consistent with the hypothesis of a multi‐component behavioural defence. The other two species showed no detectable responses to waterborne predator cues in either adult or larval stages. Larvae of these unresponsive species were significantly more vulnerable to this predator than was C. mollis. 6. For these mosquitoes, species appear either to have been selected for multi‐component defences against predation or to act in ways that could be called predator‐naïve.